Aspectos científicos y èticos de la epidemia del Virus de Inmuno Deficiencia Humana (VIH) y el Síndrome de Inmuno-Deficiencia Adquirida (SIDA) Hacia una propuesta autènticamente humana - Chomali Garib, Fernando (Medicina e Morale, 2004)
The knowledge of scientific and ethical aspects of epidemic due to the Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) is a priority in the beginning of the XXI century. This is a disease that caused big suffering both patients and their family, besides all society. This epidemic has emphasized the kind of society that we are constructing and the life styles that it is proposing. A really human proposal, to oppose this epidemic, should recognise that there is a close correlation between human behaviours and the diffusion of the disease. On the other hand, we have to wonder if the preventive strategies (especially the proposed use of condom), used to defeat epidemic, are adequate. The answer is that this method is not adequate, first of all, because it doesn't respect the dignity of the human person and, secondly, because it is not efficacious. As a matter of fact, by the use of condom people have only achieved a false safety about their sexual behaviours, banalizing their meanings and the value of the person. Making up for the value of chastity and the value of married life means making the dignity of man and women, of human sexuality and of human love. Then, this is the most safety way to defeat this epidemic. This article emphasizes the capacity of man as a whole to recognize the Good, the Truth and the Beauty which are typical of a entirely human sexuality.